POSSIBILITIES OF THE MINIMALLY INVASIVE SURGERY IN THE TREATMENT OF SEVERE FOREFOOT DEFORMITIES IN THE RHEUMATOID ARTHRITIS PATIENTS - S. Y. Berezhnoy (Travmatologiâ i Ortopediâ Rossii, 2016)
Introduction. Approximately 90% of the rheumatoid arthritis patients present with foot symptoms. Rheumatoid foot is characterized by toe dislocations and chronic wounds due to the corticosteroid treatment. In case of surgical intervention metatarsophalangeal joints excision arthroplasty remains the standard. To perform second through fifth metatarsal head resection extensive transverse plantar or longitudinal dorsal incisions are routinely used. The rate of the wound-healing problems after rheumatoid foot surgeries is 23-45%. The purpose of this study was to demonstrate the possibilities and advantages of the rheumatoid arthritis patients with severe forefoot deformities minimally invasive surgical treatment and to develop mini-invasive approach for central metatarsal heads resection. Material and methods. By the example of 23 rheumatoid arthritis female patients (30 feet) surgical treatment possibilities of percutaneous techniques in severe forefoot deformities correction were demonstrated. The average age of the group was 54.5 years (range, 39 to 72). There were 24 primary surgeries and 6 repeated. Four feet had chronic wounds. Percutaneous techniques were used to correct all the forefoot deformities components but central metatarsal head resections (7 cases). To make them minimally invasive plantar approach has been developed. Surgical technique of the central metatarsal heads resection using proposed approach was presented. Decision-making algorithm for choosing appropriate surgical technique (to perform first metatarsophalangeal arthrodesis with central metatarsal heads resection or joint-preserving surgery) was proposed, including functional test, performed under fluoroscopic control and tricks for the dislocated fifth toe reduction. Results. The mean follow-up was 12 months (range, 3 to 52). The average hospital stay was 1.23 days. No infectious or wound-healing problems were noted. Chronic wounds have healed in four weeks after surgery. Overall, patients were satisfied with the result of the 12 surgical interventions and satisfied with reservations with the result of 18 surgeries. Unsatisfactory results were not noted. Average preoperative AOFAS score was 23.7 points (range, 0 to 34); postoperative 79.2 points (range, 52 to 100), the average AOFAS score increase was 55.5 points. Conclusions. Percutaneous techniques allow correction of nearly all severe forefoot deformities components in rheumatoid arthritis patients, eliminating the need for first and fifth metatarsal head resection and significantly reducing the need for central metatarsal head resection. If central metatarsal head excision is necessary, they can be removed using minimally invasive 2-3 сm plantar approach, proposed by the author, thus reducing the risk of wound-healing complications.